SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) TERHADAP PENURUNAN NYERI PASIEN POST OPERASI - Dwi Mulianda; Ainnur Rahmanti; Alysa Tiara (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2022)
Almost all surgeries cause pain, the pain that is felt is the result of the incision. The effects of pain that do not subside are myocardial ischemia, increased morbidity, and hopelessness. One intervention to relieve postoperative pain is Spiritual Emosional Freedom Technique (SEFT). The purpose of this case study is to describe the reduction in pain scale of postoperative patients in Nusa Indah Room TK.III 04.06.02 Bhakti Wira Tamtama Semarang Hospital after SEFT intervention. This type of research is descriptive using a case study approach. The subjects in this study were 2 postoperative patients with criteria of moderate to high pain. Analysis of pain measurements using the Numerical Scale Branch scale. The analysis showed that there was a decrease in pain scale after the intervention. On subject 1 the pain scale 7 (high pain) became the pain scale 4 (moderate pain) and subject 2 the pain scale 8 (high pain) became the pain scale 4 (moderate pain). Effective SEFT therapy is used to reduce postoperative pain in the room because it is easy and simple. Good therapy is applied by nurses in the room to reduce the scale of pain in postoperative patients.